Replacing the ideology of information by exploring domains of knowledge: A case study of the periodization of Philippine history and its application to information studies - Luyt, Brendan (2015)
Purpose – This paper examines the structure of Philippine historiography as viewed by Filipino historians. The purpose of this paper is to develop an understanding of the knowledge domain of Philippine history and in particular how its practitioners organize their field of study in terms of periodization. At the end of the paper an application of this analysis is proposed, the development of an online encyclopaedia of Philippine history. Design/methodology/approach – Interviews were arranged with willing historians at two of the premier institutions of higher learning in the Philippines: the Ateneo de Manila and University of the Philippines. The historians were asked three general questions: what in their opinion, are the key defining events in Philippine history? What are the key historians for each of those events? And what are the key debates regarding these events? For the purpose of this paper it is the results of the first question that are in focus as it deals with one of the fundamental tools of historical analysis, periodization. Findings – Philippine history was found to be periodized in a variety of ways, from the traditional to other approaches that stress either Filipino rather than colonial agency or the uneven trajectories of historical development that depend on region, class, or language group. A final approach viewed Filipino history as a network of relations spanning space and time. Wikis designed around the results of domain analysis make it possible to provide information on topics of importance to a discipline as well as reveal something of its deeper structure. Combined with traditional concerns, such as use of appropriate sources, this would serve to help develop a deeper awareness of the nature of knowledge production. Originality/value – This paper represents both a contribution to the study of knowledge domains, as well as an application of that study to the work of information professionals. Putting the spotlight on Philippine historians and history also helps the LIS discipline to move away from its traditional North American and European focus. Studies of knowledge producing bodies in the rest of the world are important and overdue.